2015
DOI: 10.4103/0971-5916.162099
|View full text |Cite
|
Sign up to set email alerts
|

Immunological & metabolic responses to a therapeutic course of Basti in obesity

Abstract: Background & objectives:Basti (medicated enema) is a popular Ayurvedic intervention recommended for obesity. However, there are no data to show whether any physiological or biochemical changes occur following this treatment. This study was conducted to identify the immunological and metabolic changes in obese individuals after a therapeutic course of Basti.Methods:Thirty two obese individuals (18 and 60 yr) with a body mass index (BMI) ≥30 kg/m2 who received a therapeutic course of 16 enemas (Basti) followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The interventions include therapeutic cleansing procedures (known as Panchakarma) 6 and certain immunomodulators 7 (known as Rasayana). Local 8 and systemic 9 interventions to boost the immune system have been advocated to manage respiratory illnesses. The choice of specific Ayurveda therapeutic agents and practices is based on certain individual genetic characteristics known as Dosha Prakriti types (Vata, Pitta, and Kapha).…”
Section: Introductionmentioning
confidence: 99%
“…The interventions include therapeutic cleansing procedures (known as Panchakarma) 6 and certain immunomodulators 7 (known as Rasayana). Local 8 and systemic 9 interventions to boost the immune system have been advocated to manage respiratory illnesses. The choice of specific Ayurveda therapeutic agents and practices is based on certain individual genetic characteristics known as Dosha Prakriti types (Vata, Pitta, and Kapha).…”
Section: Introductionmentioning
confidence: 99%
“…A detail study on intervention with Panchakarma procedure -Basti-in obese individuals have documented that this procedure has modulated the immune response by regulating pro inflammatory cytokines, immunoglobulins and functional properties of T cells. These changes are associated with loss of weight, which is maintained even after 3 months after treatment [17]. Panchakarma treatment has been used in heart failure reversal in chronic heart failure patients with low ejection factor.…”
Section: Discussionmentioning
confidence: 99%
“…The herbs chosen for treatment were effective on various skin diseases and known to have immunomodulatory and anti-inflammatory effects [7][8][9][10][11][12]. He was also treated with a well-known Ayurvedic detoxifying treatment modality of Panchakarma [13][14][15][16][17][18][19]. The patient continued this treatment for last 20 years and is in fit physical condition without further appearance of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the concept of Panchakarma was also explored and basti (enema) was shown in a clinical trial to produce significant weight reduction as also significant decrease in serum interferon (IFN)-Y and interleukin (IL6), and gradual reduction in IL8 level suggesting that basti reduced pro-inflammatory cytokines which are raised in obesity (Thatte et al, 2015). In another study, Rasasindura (made of mercury and sulphur) was shown to have the same structure as non-toxic HgS and toxic chemical forms of mercury were completely absent in the study sample and nano-crystal units of Rasasindura were free of organic molecules (Ramanan et al, 2015).…”
Section: Ayurvedic Biologymentioning
confidence: 99%